2012
DOI: 10.3945/an.112.002238
|View full text |Cite
|
Sign up to set email alerts
|

Biological Determinants Linking Infant Weight Gain and Child Obesity: Current Knowledge and Future Directions

Abstract: Childhood obesity rates have reached epidemic proportions. Excessive weight gain in infancy is associated with persistence of elevated weight status and later obesity. In this review, we make the case that weight gain in the first 6 mo is especially predictive of later obesity risk due to the metabolic programming that can occur early postpartum. The current state of knowledge regarding the biological determinants of excess infant weight gain is reviewed, with particular focus on infant feeding choice. Potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
95
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 151 publications
(188 reference statements)
4
95
1
3
Order By: Relevance
“…Finally, Kerr et al (48) also found that baseline information such as child and maternal BMI, maternal age and education, and child health were the strongest predictors of onset and resolution of obesity in the school years with perinatal, breast-feeding and lifestyle exposures not being predictive. It is possible that early obesity in MexicanAmerican infants and toddlers, which is correlated to higher later obesity (16)(17)(18)(19)(20)(21)(22) , relates more to genetic or parental factors or simply that Mexican-American parents are more prone to under-reporting offering high-energy …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Kerr et al (48) also found that baseline information such as child and maternal BMI, maternal age and education, and child health were the strongest predictors of onset and resolution of obesity in the school years with perinatal, breast-feeding and lifestyle exposures not being predictive. It is possible that early obesity in MexicanAmerican infants and toddlers, which is correlated to higher later obesity (16)(17)(18)(19)(20)(21)(22) , relates more to genetic or parental factors or simply that Mexican-American parents are more prone to under-reporting offering high-energy …”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that rapid weight gain in infancy correlates with obesity in childhood and adulthood (16)(17)(18)(19)(20)(21)(22) . The time of onset and causes of early obesity are uncertain, but one study identified a median 'tipping point' of 22 months for the infant transition to overweight, which decreased to 15 months when adjusted for infants who were overweight by the first physician visit (23) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity in infants is a controversial topic; however, research supports a link between rapid early infant growth and later obesity. [60][61][62][63] Feeding. There are concerns with diagnosing obesity in infancy because of the unintended consequence of a mother's restricting food intake during infancy; restriction of fat intake can adversely impact brain development.…”
Section: Obesity Prevention Measures In Early Lifementioning
confidence: 99%
“…This period conveyed significantly more risk than weight gain between 0 and 2 months, and between 4 and 6 months, suggesting that 2 to 4 months may be an especially critical period for differences in weight trajectory on later obesity. 32 Ultimately, whether these differences in weight and weight-for-length persist to influence BMI later in childhood needs to be determined.…”
mentioning
confidence: 99%